Clinical Manifestations of Neuropsychiatric Systemic Lupus Erythematosus in Chinese Patients - Wei FAN,; Zhenyuan ZHOU,; Liangjing LU,; Shunle CHEN,; Chunde BAO, (Archives of Rheumatology, 2014)
Objectives: This study aims to describe the clinical manifestations, laboratory abnormalities, and therapeutic responses of neuropsychiatric systemic lupus erythematosus (NPSLE) among Chinese population. Patients and methods: We retrospectively reviewed the medical records of 1,772 patients, who suffered from systemic lupus erythematosus (SLE) admitted to the Department of Rheumatology of Shanghai Renji Hospital between January 1999 and December 2011. Seventy-six patients were diagnosed with NPSLE. Demographic characteristics of the patients and clinical manifestations were analyzed and laboratory abnormalities were recorded. Results: These patients had not only common SLE symptoms, but also 14 types of neuropsychiatric (NP) presentations. Proteinuria (61%), fever (55%), and infection (47%) were frequent SLE-related symptoms, while seizure (47%), delirium (26%), and headache (18%) were frequently seen NP presentations. These patients also presented abnormal laboratory tests, including positive antinuclear antibodies (78%), low levels of serum complement-3 (76%), abnormal erythrocyte sedimentation rate (68%), and higher levels of serum immunoglobulin G (59%) as well as abnormal cranial magnetic resonance imaging findings (58%). Following treatment with corticosteroids, immunosuppressants, anti-epileptics, and antipsychotics, 53 patients survived and most of them had no NP-related sequels. Conclusion: Patients with NPSLE may display various clinical manifestations and laboratory abnormalities. These patients can be effectively treated with corticosteroids and immunosuppressants.